Is the Meeting of Religions Possible? - Devaraja, N. K. (Journal of Dharma, 1975)
The issue raised in the title of the this paper constitutes not merely an academic, but a practical problem of great urgency, particularly in the context of our national life. The recent upsurge of communal violence in several parts of the country has once more brought into focus the need of thinking out ways and means for promoting harmony, among different countries and groups that make up our multi-religious society. This is not to say that our discussion should ignore the academic or theoretical aspects of the problem; however, to, the extent to which religion constitutes a practical concern, theoretical reflection on the issue under reference cannot be divided from consideration of the practical consequences of discord and strife among, followers of different religions.